ANALISIS FAKTOR PENENTU SIKAP DAN NIAT PERILAKU UNTUK MENGGUNAKAN APLIKASI KEDAI KOPI LOKAL DI JAKARTA - Pamungkas, Ilham Dwi; Suhud, Usep; Kasofi, Adnan (Yayasan Education and Social Center, 2025)
This study aims to analyze and examine the factors that influence attitude and behavioral intention to use local coffee shop applications in Jakarta. The research method used is a quantitative approach through the distribution of questionnaires. The sampling technique employed is purposive sampling, resulting in a total of 309 respondents. The population in this study consists of consumers who use the Tomoro Coffee application and reside in the DKI Jakarta area. This research utilizes SPSS version 27 and SEM (Structural Equation Modeling) with the AMOS software to analyze and process the data. The results of this study show the following: First, social influence, perceived ease of use, and system quality have a positive and significant effect on attitude. Second, perceived ease of use and attitude have a positive and significant effect on behavioral intention to use. Third, social influence and system quality do not have a direct effect on behavioral intention to use. The implications of this research offer new perspectives on the factors that influence users' intention to use local coffee shop applications, which can serve as practical references for app developers and tech companies in formulating product development strategies and enhancing user experience.